Establishment of science parks in the federal region of Kurdistan - Almas Heshmati (Institute for the Study of Labor (IZA), 2007)
New growth models consider the role of technology in production. The link between product flows and information flows in international trade suggests investment in information technology as a leading sector in the developing countries growth. Several studies establish relationships between technology applications, capital formation and economic growth. Therefore establishment of Science Parks is relevant to the investment policies directed towards a rapid economic development. However, a new industrial technology policy and participation in the globalization process must be accompanied by market reforms, organizational change and comprehensive investment in human resources and other development infrastructures to raise production capacity and capability of the labour force to achieve a sustainable knowledge based economic development in the long-run. This essay proposes establishment of Science Parks in the Federal Region of Kurdistan and discusses necessary conditions for such investment to become fruitful and with expected impacts on the region's economic development.
Keywords: D83; 330; Science parks; economic development; information technology; industrialization; Technologiezentrum; Standortpolitik; Kurdistan (Irak)